Effects of grain size and partial amorphization on elastocaloric cooling performance of nanostructured NiTi. (1st March 2022) - Lin, Hongyang; Hua, Peng; Sun, Qingping
Abstract: We fabricate three polycrystalline superelastic NiTi samples with average grain sizes of 110, 60, 35 nm and one crystalline-amorphous NiTi nanocomposite sample to investigate their elastocaloric cooling performance under compression. It is found that grain refinement and partial amorphization can notably improve coefficient of performance ( COP ) and cyclic stability with decrease in adiabatic temperature change ( ΔT ). The decrease in ΔT is caused by the decrease in austenite and reduction in transformation in small grains. The increase in COP results from the change from discontinuous to continuous phase transformation. The enhancement in cyclic stability stems from suppression of dislocations. Of the four samples, the 35 nm-grain-size one demonstrates the best elastocaloric cooling performance where ΔT reaches 19 °C and COP increases from 7 to 19 in 10 4 cycles under 1200 MPa. The study shows that the elastocaloric cooling performance of NiTi can be enhanced via grain refinement through controlled thermomechanical processing. Graphical abstract: Image, graphical abstract